Is South Africa Receiving More than Its Fair Share of Portfolio Flows? - Gray, Gavin; Asonuma, Tamon (Washington, D.C. : International Monetary Fund, 2011)
This paper develops an empirical model of the drivers of portfolio flows, and concludes that South Africa has indeed received greater bond flows than can be explained by macroeconomic fundamentals. Bond flows in the four quarters through 2010:Q3 not only exceeded the average over the past 10 years, but also deviated significantly from the amount implied by explanatory variables, including the fiscal balance, the difference between the country's and world GDP growth rates and a summary indicator of external vulnerabilities. Some capital market factors specific to South Africa irrelevant to macro variables, such as size of capital market, which are reflected in remarkably high fixed effect compared to other emerging countries, have contributed to attracting equity flow.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet